Anthropogenic effects on the feeding habits of wolves in an altered arid landscape of central Iran - Tourani, Mahdieh; Moqanaki, Ehsan M.; BOITANI, Luigi; CIUCCI, Paolo (mammalia, 2013)
We determined the diet of the poorly-studied Middle Eastern wolves (Canis lupus) in central Iran in 2009-2010. Food items consisted mainly of farmed chicken and domestic goat (i.e., anthropogenic resources) using both qualification and quantification methods. In contrast, we identified the remains of wild ungulates in negligible quantities. Our data simulations showed that poultry and goats are both primary food items of wolves in the study area. The relative importance of main prey items did not vary seasonally, and, although there were some minor differences in secondary food items, we did not reveal any seasonal effect in diet composition. The negligible consumption of wild prey strongly suggests that wolves are not, at present, a limiting factor for wild prey in our study area. Appropriate management of illegal dumping, in conjunction with excluding wolves and other carnivores from human refuse, would minimize the chance of human-carnivore encounters, wolf-livestock conflicts and, in turn, the persecution of carnivores. Our study contributed to our knowledge of the feeding ecology of the Middle Eastern wolves in areas with a relatively high abundance of anthropogenic foods and a moderately low abundance of wild prey.